Kur'an'da "Birr" Kavramı Üzerine Semantik Bir Analiz - Okumuş, Mesut (Dinî araştırmalar, 2002)
In this paper, we studied the ‘birr’ concept in the Qur’an; its semantical structure before and after Qur’anic usage and its relations with other concepts. The content and meaning of the word that used at the cahiliyan poets has been changed fay the Qur’an. Thus, in addition to its horizontal dimension at the cahiliyan period, it acquired vertical that is a heavenly dimension and became a basic concept in the Qur’an, especially during the Medinean period. Its usage in the Medinean verses provides/indicates that its meaning scope extended that contains creedings, devotions and ethical principles of Islam